2013
DOI: 10.1103/physrevb.88.214301
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics of a microelectromechanical oscillator with delayed feedback

Abstract: We study the dynamics of a nonlinear electromechanical oscillator with delayed feedback. Compared to their linear counterparts, we find that the dynamics is dramatically different. The well-known Barkhausen stability criterion ceases to exist, and two modes of operation emerge: one characterized by hysteresis in combination with a bistable frequency and amplitude; the other, by self-stabilization of the oscillation frequency and amplitude. The observed features are captured by a model based on a Duffing equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…In this case, the oscillator will work in a bistable state [33]. This was also observed in figure 4, where, as the jump approached, the presence of the high-frequency motion started to be visible (green line).…”
Section: Nyquist Stability Criterionsupporting
confidence: 50%
See 1 more Smart Citation
“…In this case, the oscillator will work in a bistable state [33]. This was also observed in figure 4, where, as the jump approached, the presence of the high-frequency motion started to be visible (green line).…”
Section: Nyquist Stability Criterionsupporting
confidence: 50%
“…The single-degree-of-freedom equation of motion that describes the vibration of the cantilever immersed in a viscous fluid in the feedback loop is therefore given by [33] (13) where the dot stands for time derivative and F(t) is the forcing term from the dither piezo. m CT = LWTρ c is the total mass of the beam, where T and ρ c are, respectively, the thickness of the beam and the density of the constituent material, while c i = 2πf 0i m CT /Q i , k i = (2πf 0i ) 2 m CT and y i are the intrinsic damping coefficient, stiffness and displacement associated to the i-th resonance mode, respectively.…”
Section: Dynamical Numerical Model: Hydrodynamic Forcementioning
confidence: 99%
“…In particular, it has been highlighted that the microcantilever dynamic response is strongly affected by the delay present in the feedback loop. [12][13][14] In this work, it is shown how the nonlinear dynamics of a cantilever embedded in a feedback loop with an adjustable phase-shifter can be used as a high-sensitivity or threshold rheological sensor. The frequencies of the oscillations in the feedback loop are studied as a function of the viscosity of different water-glycerol solutions and the delay that is introduced in the loop by the phase-shifter.…”
mentioning
confidence: 99%
“…One of the main drawbacks of using feedback loops to improve sensing performance is the presence of different sources of nonlinearities introduced, for example, by the nonlinear electronic components required to process the signals or even by the intrinsic mechanical nonlinearities of the resonator. The analysis of the dynamics of microresonators in presence of mechanical nonlinearities has shown interesting and surprising phenomena, such as stable operation of the resonators far beyond the critical vibration amplitude [24], [25] or bistable regimes [26], [27]. It was also shown that the frequency of oscillation is strongly dependent on the delay affecting the feedback signal [27]- [29].…”
Section: Introductionmentioning
confidence: 99%